PENGARUH AUDIT FEE, FINANCIAL DISTRESS, OPINI AUDIT, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY - Gabriella Stefanie Purba (2022)
This study is a quantitative study that aims to analyze the factors that effect of effect of audit fee, financial distress, audit opinion, and firm size on audit delay in trading, service, and investments companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses secondary data in the form of company annual reports. The sample of this study is 104 companies. Hypothesis testing in this study is using Multiple Linear Regression Analysis with STATA program. The result of data analysis indicate that (1) audit fee has has no significant effect on audit delay, (2) financial distress has has no significant effect on audit delay, (3) audit opinion has a negative and significant effect on audit delay, (4) firm size has has no significant effect on audit delay.